Simulation of Thermodynamics Aspects about Pulse Tube Refrigerator - Hozumi, Yoshikazu; Shiraishi, Masao; Murakami, Masahide (Advances in Cryogenic Engineering; Volume 49B, 2004)
In order to investigate the heat transfer mechanism inside a pulse tube refrigerator, CFD has been applied to simulate the working gas behavior. Three dimensional compressible Navier-Stokes equations with viscous dissipation have been solved. Heat conduction between the working gas and the tube metal solids are incorporated into the simulation. A Stirling cycle refrigerator has been also simulated to validate the heat transfer mechanism of the pulse tube refrigerator. However, there is a distinctive heat transfer from the cold end to the hot end of pulse tube, the pulse tube works as a gas displacer to induce a phase shift. The heat transfer of pulse tube refrigerator is caused by the same mechanism of Stirling cycle refrigerator. Additionally, thermal convection at an inclined pulse tube on the angle less than horizontal installation is investigated to show simulation capability of the three dimensional modeling.